2013
DOI: 10.13045/acupunct.2013050
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Correlation between Surface Electromyography and Assessment Scale for Facial Palsy

Abstract: Objjectives : The purpose of this study is to investigate the correlation between surface electromyography(SEMG) and assessment scales for facial palsy. Methods : The subjects for this study were 21 patients who had peripheral facial nerve palsy. We analyzed about the correlation between the results of SEMG and facial nerve assessment scales that were carried out at the same time. The assessment scales used in this study were House-Brackmann scale, Yanagihara grading system, Sunnybrook facial grading system. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…15,16 Recently, there and reported that there was a significant correlation, which is in agreement with the results of the current study. 19 The greatest correlation was shown in the frontalis muscle (r = 0.567, p < 0.01), while the lowest correlation was found in the nasalis muscle (r = 0.393, p < 0.02). The frontalis muscles are bigger than other facial muscles and independently located.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…15,16 Recently, there and reported that there was a significant correlation, which is in agreement with the results of the current study. 19 The greatest correlation was shown in the frontalis muscle (r = 0.567, p < 0.01), while the lowest correlation was found in the nasalis muscle (r = 0.393, p < 0.02). The frontalis muscles are bigger than other facial muscles and independently located.…”
Section: Discussionmentioning
confidence: 89%
“…Each participant was asked to activate their muscles for 5 seconds and then relax for 5 seconds (As in previous study, the frontalis; raises eyebrows, the orbicularis oculi; closes eyes, the nasalis; compress the nasal cartilages, the orbicularis oris; pucker the lips, all muscles contraction was instructed to do as much as possible). 19 This test was carried out three consecutive times.…”
Section: ) Surface Emg Evaluationmentioning
confidence: 99%
“…In contrast, there is no pain induction, and the method is simpler than the conventional nEMG, which makes it easy to repeat measurement and follow-up because sEMG is a non-invasive method that attaches electrodes to the skin surface [ 5 , 6 , 8 ]. Nikolaus et al [ 19 ] Have proposed a new direction of facial sEMG studies by studying the facial EMG patterns of normal people using the sEMG devices, Kim et al [ 10 ] Suggested the possibility of sEMG as an assessment tool of facial nerve palsy by analyzing the correlation between sEMG and clinical assessment scale.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the exercise and rehabilitation of the musculoskeletal system have been actively conducted using the characteristics of sEMG. There are studies on the use of sEMG in the facial muscles, such as the location of the electrodes [ 8 , 9 ], the types of electrodes, Frigerio A et al [ 10 ] Have studied the sEMG of the orbicularis oculi m. and subsequently, in Korea, Kim et al studied the motion of the orbicularis oris m. of health people. In a study for facial nerve palsy, Kim et al [ 11 ] reported the correlation between sEMG and clinical assessment scale of facial nerve palsy in 21 patients within 90 days of onset.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been attempts to interpret results of the sEMG test on patients with facial paralysis by associating with the naked eye test, it was insufficient to represent the sEMG test with the smaller number of samples of 21 people. Another ongoing study on the sEMG measurements of 20 males and 40 females with good health when they move their facial parts was designed to draw biological electric features of the local specimen with good health but shows its limitation in that it fails to provide no classification other than classification by males and females as well as with the smaller number of specimen [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%